Colistin Susceptibility in Companion Animal-Derived Escherichia coli, Klebsiella spp., and Enterobacter spp. in Japan: Frequent Isolation of Colistin-Resistant Enterobacter cloacae Complex - Toyotaka Sato; Toyotaka Sato; Toyotaka Sato; Kazuki Harada; Masaru Usui; Shin-ichi Yokota; Motohiro Horiuchi; Motohiro Horiuchi (Frontiers in Cellular and Infection Microbiology, 2022)
Transmission of colistin-resistant Enterobacterales from companion animals to humans poses a clinical risk as colistin is a last-line antimicrobial agent for treatment of multidrug-resistant Gram-negative bacteria including Enterobacterales. In this study, we investigated the colistin susceptibility of 285 Enterobacterales (including 140 Escherichia coli, 86 Klebsiella spp., and 59 Enterobacter spp.) isolated from companion animals in Japan. We further characterized colistin-resistant isolates by multilocus sequence typing (MLST), phylogenetic analysis of hsp60 sequences, and population analysis profiling, to evaluate the potential clinical risk of companion animal-derived colistin-resistant Enterobacterales to humans in line with the One Health approach. All E. coli isolates were susceptible to colistin, and only one Klebsiella spp. isolate (1.2%, 1/86 isolates) was colistin resistant. Enterobacter spp. isolates were frequently colistin resistant (20.3%, 12/59 isolates). In colistin-resistant Enterobacter spp., all except one isolate exhibited colistin heteroresistance by population analysis profiling. These colistin-heteroresistant isolates belonged to clusters I, II, IV, VIII, and XII based on hsp60 phylogeny. MLST analysis revealed that 12 colistin-resistant Enterobacter spp. belonged to the Enterobacter cloacae complex; five Enterobacter kobei (four ST591 and one ST1577), three Enterobacter asburiae (one ST562 and two ST1578), two Enterobacter roggenkampii (ST606 and ST1576), and Enterobacter hormaechei (ST1579) and E. cloacae (ST765) (each one strain). Forty-two percent of the colistin-resistant E. cloacae complex isolates (predominantly ST562 and ST591) belonged to lineages with human clinical isolates. Four E. kobei ST591 isolates were resistant to third-generation cephalosporines, aminoglycosides, and fluroquinolones but remained susceptible to carbapenems. In conclusion, our study is the first to our knowledge to report the frequent isolation of the colistin-resistant E. cloacae complex from companion animals. Furthermore, a subset of isolates belonged to human-associated lineages with resistance to multiple classes of antibiotics. These data warrant monitoring carriage of the colistin-resistant E. cloacae complex in companion animals as part of a domestic infection control procedure in line with the One Health approach.